2003
DOI: 10.1046/j.1471-4159.2003.01648.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity‐dependent nucleocytoplasmic shuttling of HDAC4 and HDAC5

Abstract: The class II histone deacetylases, HDAC4 and HDAC5, directly bind to and repress myogenic transcription factors of the myocyte enhancer factor-2 (MEF-2) family thereby inhibiting skeletal myogenesis. During muscle differentiation, repression of gene transcription by MEF-2/HDAC complexes is relieved due to calcium/calmodulin-dependent (CaM) kinase-induced translocation of HDAC4 and HDAC5 to the cytoplasm. MEF-2 proteins and HDACs are also highly expressed in the nervous system and have been implicated in neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
262
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(283 citation statements)
references
References 47 publications
20
262
1
Order By: Relevance
“…The results of the present work further substantiate HDAC4 as a specific direct substrate of CaMKII␦, based on the finding that HDAC4 phosphorylation was abolished in cardiac extracts from CaMKII␦-KO mice, whereas HDAC5 phosphorylation was unaffected. Others have reported that CaMKII induces cytosolic accumulation of both HDAC4 and HDAC5 (19,37,38). Because HDAC5 can acquire CaMKII responsiveness by oligomerization with HDAC4 (20), the nuclear export of HDAC5 in response to CaMKII signaling may reflect, at least in part, this type of indirect mechanism of HDAC5 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present work further substantiate HDAC4 as a specific direct substrate of CaMKII␦, based on the finding that HDAC4 phosphorylation was abolished in cardiac extracts from CaMKII␦-KO mice, whereas HDAC5 phosphorylation was unaffected. Others have reported that CaMKII induces cytosolic accumulation of both HDAC4 and HDAC5 (19,37,38). Because HDAC5 can acquire CaMKII responsiveness by oligomerization with HDAC4 (20), the nuclear export of HDAC5 in response to CaMKII signaling may reflect, at least in part, this type of indirect mechanism of HDAC5 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas neuronal activity-dependent nucleocytoplasmic shuttling of HDAC4 and HDAC5 was induced through both L-type calcium channels and synaptic N-methyl-Daspartic acid receptors, differences in the activation thresholds for HDAC4 and HDAC5 nuclear export were observed (Chawla et al, 2003). Another neuronal signaling pathway converges on class IIa HDACs.…”
Section: Signalingmentioning
confidence: 98%
“…This diversity allows class IIa HDACs to respond to different signaling pathways, with each signaling pathway providing a functional relevance for a given kinase. Some kinases have been shown to act preferentially on specific members of the class IIa family, which emphasizes the importance that distinct class IIa HDACs may have in specific genetic programs (Chawla et al, 2003;Liu et al, 2005;. CaMKII, for example, is able to drive HDAC4, but not HDAC5, out of the nucleus, probably because HDAC4 possesses a nonconserved CaMKII-binding site (Backs et al, 2006).…”
Section: Subcellular Distributionmentioning
confidence: 99%
“…In addition to regulating the cell cycle, calcium signaling also can regulate the nuclear transport of proteins. For example, increases in intracellular calcium result in translocation of histone deacetylase 5 (HDAC5) from the nucleus to the cytoplasm in cultured hippocampal neurons [17]. In contrast, increases in intracellular calcium result in nuclear accumulation of human transducer of regulated CREB (TORC) proteins [18] and nuclear factor of activated T-cells (NF-AT) [19].…”
Section: Introductionmentioning
confidence: 99%